Pengaruh Orientasi Ekonomi dan Kesadaran Lingkungan terhadap Produktivitas dan Rendemen Tebu Rakyat Pabrik Gula Wonolangan - Ungki Prabowo Putra; Irham Irham; Lestari Rahayu Waluyati (Universitas Muhammadiyah Yogyakarta, 2019)
The increasing of sugarcane productivity and yield is not only affected by factors of production such as seeds, fertilizer, labors, and herbicides. Other factors such as economic orientation and environmental awareness also show their effects on sugarcane productivity and yield. This research was conducted to determine the effect of economic orientation and environmental awareness both on productivity and yield of sugarcane community partners in the Wonolangan Sugar Factory. The study was conducted in Probolinggo and Lumajang Regency with 102 samples of farmers selected using simple random sampling. The measurement of the level of economic orientation and environmental awareness was carried out using Likert scale and was categorized as low, medium and high. The influence of economic orientation and environmental awareness both on productivity and yield of sugar cane were analyzed using multiple regression with the Cobb Douglas production function. Based on the results, the economic orientation and environmental awareness of farmers were relatively high and could increase sugarcane productivity and yield.